2019
DOI: 10.1177/1477760619895026
|View full text |Cite
|
Sign up to set email alerts
|

Waste tires pyrolysis oil as a source of energy: Methods for refining

Abstract: A huge amount of waste tires is generated every day in the world. This determines the search for ways to use them. The extended process of production and application of scrap tires leads to their significant mass accumulation, thus representing environmental risk. Tires are inert materials, extremely difficult to treat, and nonbiodegradable. In recent years, many plants have been built for processing, treatment, and utilization of this kind of waste. A problem has emerged to find a suitable, environmentally fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Narani et al ( 2020 ) concluded that textile fibers from ELTs could enhance the geotechnical characteristics of the expansive soil. Toteva and Stanulov ( 2020 ) explored environmentally friendly applications of ELT pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Narani et al ( 2020 ) concluded that textile fibers from ELTs could enhance the geotechnical characteristics of the expansive soil. Toteva and Stanulov ( 2020 ) explored environmentally friendly applications of ELT pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to the rubber composition in the waste tires (WT), the HV of waste tire pyrolysis oil (WTPO) is ca. 30 to 42 MJ/kg, which is competitive with other conventional fuel types (HV diesel = 47 MJ/kg and HV gasoline = 45 MJ/kg), especially lignite coal and biomass, which have lower caloric values at 26.8 and 16.7 to 19.0 MJ/kg, respectively 3‐5 …”
Section: Introductionmentioning
confidence: 99%
“…30 to 42 MJ/kg, which is competitive with other conventional fuel types (HV diesel = 47 MJ/kg and HV gasoline = 45 MJ/kg), especially lignite coal and biomass, which have lower caloric values at 26.8 and 16.7 to 19.0 MJ/kg, respectively. [3][4][5] Since the direct burning of WT generates the toxic gases to be harmful for human or animal health and environment, 6 the transformation of WT via pyrolysis is a more environmental friendly process to produce high yield of alternative liquid fuels up to 38%. 7 However, the increasingly stringent environmental policies to control the amounts of aromatics and sulfur or nitrogen species presented in the fuels limit the utilization of untreated WTPO.…”
Section: Introductionmentioning
confidence: 99%
“…It was predicted that the number of waste tires (WTs) would exceed 1.6 billion in 2024, and the increase would reach 20% by 2030 . Various economic and environmental problems were aggravated due to the increasing quantity of WTs and inappropriate recycling methods in the long term. Therefore, it is significant for WT disposal to explore effective, profitable, and environmentally friendly methods.…”
Section: Introductionmentioning
confidence: 99%